2008
DOI: 10.1179/crn.2008.028
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Replacement Therapy Among Post-menopausal Women and Its Effects on Signs and Symptoms of Temporomandibular Disorders

Abstract: The prevalence of temporomandibular disorders (TMD) is about two to five times higher in females than in males. Data for the higher prevalence of TMD in women and prevalence rates peak during the reproductive years and decrease after menopause. This indicated that female sex hormones may play a role in the etiology or maintenance of TMD. The aim of this study was to investigate the relationship between postmenopausal hormone use and TMD in Turkish postmenopausal women. One hundred-eighty (180), postmenopausal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
0
24
0
5
Order By: Relevance
“…The putative role of estrogen for temporomandibular joint disorders in women [53] may have multiple mechanisms, including influencing cellular events in bone metabolism ( vide supra ), as well as regulatory processes of neuralgia, myalgias, migraines, and localized or generalized pain responses [52, 56]. Hormone-replacement therapy has been reported to raise the prevalence of temporomandibular joint disorders in aging postmenopausal women, although this observation has not been confirmed [55]. …”
Section: Osteoimmunopathology and Osteoporosismentioning
confidence: 99%
“…The putative role of estrogen for temporomandibular joint disorders in women [53] may have multiple mechanisms, including influencing cellular events in bone metabolism ( vide supra ), as well as regulatory processes of neuralgia, myalgias, migraines, and localized or generalized pain responses [52, 56]. Hormone-replacement therapy has been reported to raise the prevalence of temporomandibular joint disorders in aging postmenopausal women, although this observation has not been confirmed [55]. …”
Section: Osteoimmunopathology and Osteoporosismentioning
confidence: 99%
“…Some studies have reported that exogenous hormones can increase the risk of certain pain syndromes 27 , increase the severity of self-reported pain 18, 41, 43 , and increase experimentally evoked pain sensitivity 3, 1112, 24, 34 . However, other studies have failed to demonstrate differences in pain severity, frequency, and phase modulation between women taking exogenous hormones and those without 10, 21, 23, 31 . Thus, the role of sex hormone use among women with existing pain remains unclear.…”
Section: Introductionmentioning
confidence: 94%
“…Similar to studies of naturally occurring changes in endogenous hormones, many studies have examined the effect of exogenous ovarian hormone use on pain sensitivity among healthy individuals 1112, 18, 21, 2325, 3334, 44 , whereas few studies have examined their effect among clinical populations with existing pain 10, 31, 43 . Some studies have reported that exogenous hormones can increase the risk of certain pain syndromes 27 , increase the severity of self-reported pain 18, 41, 43 , and increase experimentally evoked pain sensitivity 3, 1112, 24, 34 .…”
Section: Introductionmentioning
confidence: 99%
“…Highest TMD prevalence at reproductive age, added to the pattern of starting after puberty, higher association to pre-menstrual period and lower prevalence in the post-menopausal period suggest that female hormones may play important role in TMD etiology or maintenance 6,8,9 . In addition, gestation brings about dramatic changes in sexual estrogen and progesterone hormones.…”
Section: Introductionmentioning
confidence: 99%